Digital Fatigue and Performance Challenges in Smart Hospitals: A Workforce Resilience Perspective - Anton Nugroho; Aris Sarjito; Deni Setiawati; Lusianah Lusianah; Wenni Mustika (Poltekita: Jurnal Ilmu Kesehatan, 2026)
Background: Digital transformation in hospital systems has accelerated globally, embedding electronic health records, clinical decision-support systems, interoperability platforms, and performance dashboards into governance architectures. Leading institutions, including the World Health Organization and the Organisation for Economic Co-operation and Development, position digital health as central to system resilience and efficiency. However, growing scholarship highlights unintended consequences, including documentation burden, alert overload, and clinician cognitive strain. This study develops a governance-oriented interpretive model linking digital work intensification, digital fatigue, performance paradox dynamics, and multilevel human resource (HR) resilience in smart hospitals. Methods: A qualitative secondary analysis was conducted on 28 documents (2020–2026), comprising peer-reviewed articles, international policy reports, and institutional governance frameworks. Reflexive thematic analysis, informed by socio-technical systems theory, performance paradox theory, and workforce resilience theory, was applied to examine documents as institutional artifacts shaping accountability regimes, workload structures, and adaptive capacities. Results: Four governance-mediated dynamics were identified. First, digital work intensification emerged through expanded documentation mandates, dense alert systems, and interoperability-driven coordination complexity. Second, digital fatigue was framed as an institutional risk marked by cumulative cognitive load and relational strain. Third, a performance paradox was evident, with efficiency gains coexisting alongside workforce strain. Fourth, HR resilience, through individual coping, team buffering, and participatory IT governance, functioned as an adaptive moderator but did not eliminate structural workload misalignment. Conclusion: Workforce sustainability in digitally intensive hospitals depends less on technological sophistication than on governance alignment among accountability systems, digital infrastructure, and human capacity.